Efficacy of biofeedback as a treatment for asthma. A systematic review - Pinnock-Branford, Annielee (2021)
Asthma is a disease of the respiratory system whose symptoms include shortness of breath, chest tightness, coughing, and wheezing. Different treatments have been investigated and tested to control it, the treatment with anti-inflammatory steroids being the most used. However, biofeedback has been positioned as a treatment with clinical relevance and effectiveness. This study conducted a systematic review that included 16 articles on the use of biofeedback as a treatment for asthma. The eligibility criteria followed were: a) The dependent variable had to be asthma and use biofeedback as treatment. b) Be an experimental or quasi-experimental study and provide the sample size. c) Have a control group, pre and post-test. The results suggest that the use of respiratory biofeedback and heart rate variability is effective when it comes to mild and moderate asthma and, even more so, when accompanied by medication and other treatments such as relaxation. This implies that it could be considered as a probably effective treatment in cases where pharmaceutical treatment is not a viable option. The biggest limitation found was the lack of studies that had the necessary quality criteria for a meta-analysis, which is why a systematic review was chosen.